Disseminated Subcutaneous Rhinosporidiosis: A Case Report - Sarker, Md Moniruzzaman; Kibria, AKM Golam; Haque, Md Manzurul (TAJ: Journal of Teachers Association, 2011)
Rhinosporidiosis is a chronic granulomatous infection that frequently involves the nose and nasopharynx, and occasionally affects the other areas of the body. We report a 40-year-old patient who had disseminated subcutaneous rhinosporidiosis. The patient presented with multiple subcutaneous lesions over the different parts of the body during last five years. He had a past history of a lesion in his right nostril with nasal blockage and haemorrhage ten years back. In our surgical unit the patient had been subjected to elective operation with excision of subcutaneous lesions. The histopathology report of excised subcutaneous lesions was rhinosporidiosis. The patient is being followed up postoperatively. doi: 10.3329/taj.v19i1.3166 TAJ 2006; 19(1): 31-33